Adoption and Continued use of Mobile Technology: An Analysis of CommCare Data. (2015) - Dayalu, Rashmi; Wacksman, Jeremy; Chen, Mengji; Loudon, Melissa; Lesh, Neal
Abstract: CommCare, developed by Dimagi Inc., is an open-source mobile technology platform that supports hundreds of programs worldwide. This article used metadata to explore how CommCare is adopted and used over time by humanitarian workers in resource-poor settings. Data submitted by CommCare users between January 1, 2010 and October 31, 2014 were analysed. The first six months of CommCare usage for new workers showed a general upward trend, suggesting that sufficient training time should be considered by programs that are introducing mobile technology into their workforce. Following CommCare adoption, worker activity levels were consistent between consecutive months, giving programs a method to identify users with atypical work patterns. The findings from this analysis demonstrate the utility of mobile technology metadata, especially for programmatic design and evaluation.